Impact of the first COVID-19 lockdown period on diet and health-related behaviours of Maltese adults - Claire Copperstone; Stuart W. Flint; Adrian Brown; Fiona Sammut (Discover Public Health)
Abstract Empirical evidence has highlighted the impact of the Coronavirus (COVID-19) pandemic, specifically examining ‘lockdown periods’ enforced by Governments globally. These studies have shown that lockdowns had a disproportionate impact on subgroups of the population, which may have exacerbated health inequalities. The primary aim was to explore the impact of the first partial lockdown period (March–June 2020) on health-related behaviours in Maltese adults. A retrospective cross-sectional survey study design was employed and disseminated between September and October 2020 online. The study was approved by the University of Malta’s Faculty of Health Sciences Research Ethics Committee. A total of 358 respondents were included in the final analysis in a predominantly female sample (n = 295, 82.9%). Median body mass indices for males and females were 27.4 and 25.5 kg/m2, respectively. Approximately one third, 139 (38.8%), of respondents, claimed that they had gained weight and similarly, 140 (39.1%) reported trying to lose weight. Over a third (n = 145, 40.5%) reported increased food prices, with 53.1% also reporting moderate or high changes in food shopping behaviours (n = 190). Moderate or high changes in diet were reported by 161 (44.9%) respondents, including increased consumption of confectionery/snacks (n = 132, 62.5%). No changes in alcohol consumption were reported by the majority (n = 231, 64.5%). Nearly half (163, 45.5%) reported less physical activity carried out. These findings show some of the negative impacts the first partial lockdown had on health behaviours, the food environment and body weight in Maltese adults and have important implications for any future pandemics.